2010
DOI: 10.1038/ejcn.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trans fatty acid intake and maternal and infant adiposity

Abstract: Background/Objectives: The fatty acid composition in maternal diet and in breastmilk during lactation may be a factor in the development of childhood overweight later in life. To investigate the association between trans fatty acid and adiposity, 96 mother-infant pairs (exclusive breastfed; mixed fed; and formula fed) at 3 months postpartum were interviewed; body composition was measured onsite using the BOD POD and PEA POD for mothers and infants, respectively. Subjects/Methods: This was a cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
1
25
0
2
Order By: Relevance
“…They were symmetrically larger than the AGA infants on all anthropometric dimensions. These findings were in keeping with Anderson et al, 22 who demonstrated using ADP that infants with higher birthweight had higher body fat at 3 months of age.…”
Section: Main Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…They were symmetrically larger than the AGA infants on all anthropometric dimensions. These findings were in keeping with Anderson et al, 22 who demonstrated using ADP that infants with higher birthweight had higher body fat at 3 months of age.…”
Section: Main Findingssupporting
confidence: 82%
“…This method has been validated 16,17 and is the gold standard for measuring infant body composition. [18][19][20][21][22] In this study, we performed anthropometric measurements and determined body composition of LGA infants using ADP. We also aimed to identify antenatal predictors and short-term labour and birth outcomes associated with LGA infants.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the fat content variation in human milk is clearly the result of different dietary, metabolic and physiologic controls (German, 2011). In humans, the fatty acid composition in maternal diet and in breastmilk during lactation may not affect the infant body composition in the early postpartum period but may be a factor in the development of childhood overweight later in life (Anderson et al, 2010). The somatic maturation and reflex development from the 2nd over the 21st postnatal days of life are good indicators to understand how environmental factors can influence the functional maturity of the brain development (Smart & Dobbing, 1971;Gramsbergen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Kebanyakan penelitian mengenai pengaruh TFA hanya terkait bidang kesehatan dan masih sedikit penelitian mengenai pengaruh TFA terhadap simpanan lemak tubuh dan status gizi , akan tetapi hasil penelitian Anderson et al (2010) menunjukkan bahwa terdapat pengaruh dari asupan lemak trans terhadap komposisi lemak tubuh ibu dan bayi pasca kelahiran. Selain itu, asupan TFA juga dapat mengganggu metabolisme asam lemak esensial yang baik bagi perkembangan bayi (Innis 2006).…”
Section: Pendahuluanunclassified